PROBLEM INVESTIGATION OF CRIMINAL WASHING THAT CAME FROM THE PREDICATE CRIME BANKING BY THE INVESTIGATOR - Adi Sulistiyono, Pujiono, Ahmad Dwi Nuryanto (International Journal of Advanced Science and Technology, 2020)
The problem of investigating criminal acts of laundering from criminal acts of war crimes has several problems including the synergy between investigators not yet integrated, between the Republic of Indonesia Police investigators, the Financial Services Authority, and the Attorney General's Office, there is still overlapping authority from the three investigating institutions. Investigations can be carried out in each of the stages at the stage of placement, layering, or integration. Investigation can be carried out by each investigating institution, this depends on the case of the case. First: Cases of corruption, then, then the money was washed (money laoundring) turned out to be predicate crimenya is from the act of pidan pembangkan then those involved in the KPK and OJK. The second money laundry then the original prediakate is a crime, then the police and OJK, Thirdly, if the criminal act is divided, first it is found that then the money laundering is carried out, the initial investigator is the new OJK police. Money Laundering can also have an impact on the loss of state revenues from the tax sector, the market and international world distrust of the Indonesian state, the climate of investors becoming unwilling to invest in Indonesia.